Case report: Findings in ovaries development from an aborted equine fetus - Cuccato, Matteo; Bertuglia, Andrea; Divari, Sara; Brambilla, Eleonora; Grieco, Valeria; Bollo, Enrico; Scaglione, Frine Eleonora (Frontiers in Veterinary Science, 2024)
An aborted female foal was submitted for necropsy. At gross examination, ovaries were pale, greyish, enlarged (6x5cm) and with a well-developed vascular structure surrounding the external surface; the cut surface of ovaries showed a brownish parenchyma with white follicular areas mainly localized on the peripheral region. Ovaries were fixed for histological investigations. Histological evaluation of ovaries showed polygonal shaped cells with abundant cytoplasm and round or oval nucleus, arranged in cords of single cells. The tissue architecture was characterized by the presence of lobular-like tissue with a central vein. The tissue mimicking hepatocytes was delimited by a mature fibrous tissue and surrounded by normal ovarian tissue characterized by germinal epithelium and primordial follicular structures. Based on histological findings, a diagnosis of bilateral ovarian hamartoma was made at first. For a better characterization of the ovarian tissue, tissue-specific (liver and ovary) markers expression was investigated by immunohistochemistry. After immunohistochemistry, the hamartoma diagnosis was excluded. Ovaries showed unique characteristics, that differ from the adult horse ovaries, but also showed unique morphological features different from other mammalian species. This case report contributes to the description of ovaries at a later stage of pregnancy and unveils unique characteristics of horse ovaries development, avoiding misdiagnosis with pathological findings, hamartomas or neoplasia.